Establishment of Paediatric and Neonatal Intensive Care Units at Patan Hospital, Kathmandu: Critical Determinants and Future Challenges - Adhikari, N; Avila, ML; Kache, S; Grover, T; Ansari, I; Basnet, S (Journal of Nepal Paediatric Society, 2011)
Introduction: Although preventive medicine and primary care are priorities in developing countries, they must be supported by appropriate care of sick and extremely sick children in the medical facilities. Lack of resources and absence of skilled physicians and nurses may lead to poor outcomes in critically ill patients. Intensive care of newborns and children is thought to be very expensive with a low cost-benefit ratio. This presentation discusses the critical factors that facilitated the establishment of PICU and NICU in an urban public hospital in Nepal, where a good standard of Level 2 care was already provided. Aims and objectives: A cooperative model of creation and transfer of technology from the West to a resource-poor country was envisaged. PICU and NICU with six beds each were established. Design and setting: The Nick Simons Foundation, USA provided financial support for design, building and furnishing of a new Mother and Child Wing at Patan Hospital. A generous grant of $300,000 again by the Nick Simons Foundation helped equip the units. Donated equipments also included procedures, medication and storage carts. Methodology: A total of 22 volunteers, 21 from USA and one from Netherlands, were recruited to complete the three months of training. An extensive curriculum was prepared. The trainer team had monthly teleconferences and regular communications with the Chief of Paediatric Services and Nursing Director of Patan Hospital via e-mails and telephone. Responsibilities of volunteers and the host hospital were identified. Results: After 3 years of preparation, the project started in June 2009. All day lectures on topics in critical care, mock case scenarios, practical equipment training and simulated procedures led to the graduation of 60 nurses. Twenty five physicians were trained for three months. The expert team worked with the locals in preparing the units, arranging furniture and equipment, stocking carts, making inventory and preparing protocols. A protocol handbook was developed on topics such as mechanical ventilation, sedation, admission/discharge criteria, procedures and management of different disease states. Various charts such as nurse observation charts, notes by residents, procedure hand offs at change of shifts were designed and printed. Infection control practices and methods of sterilizing non disposable articles were identified and protocols written. At the end of three months the units were functioning with trained local manpower and reasonable modern equipment. Conclusion: Developing nations may not have enough resources to establish much needed critical care facilities. Developed countries can help by funding basic infrastructure and providing expertise in order to transfer knowledge and technology. Involvement in planning from the beginning and training at the host site is a preferred model of transfer of technology. Key words: Paediatric Intensive Care Unit (PICU); Neonatal Intensive Care Unit (NICU); Patan Hospital DOI: 10.3126/jnps.v31i1.4161 J Nep Paedtr Soc 2010;31(1):49-56